2018
DOI: 10.1016/j.actbio.2017.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of osteoclasts by osteoblast lineage cells depends on titanium implant surface properties

Abstract: In this study, we developed a novel in vitro model to study how microstructured and hydrophilic titanium implants impact bone remodeling for dental and orthopaedic applications. Our approach intersects biomaterials and systems physiology, revealing for the first time that implant surface properties are capable of regulating the communication among the cells involved in remodeling of primary bone during osseointegration. We believe that the basic research presented in our manuscript will provide important knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 53 publications
1
59
0
1
Order By: Relevance
“…Furthermore, this is the first reported use of these transcortical implants custom‐made to fit rat femurs. Scanning electron microscopy, laser confocal microscopy, and x‐ray photoelectron spectroscopy revealed a surface morphology, average surface roughness, and surface composition similar to what has been previously reported for implants processed in the same manner …”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, this is the first reported use of these transcortical implants custom‐made to fit rat femurs. Scanning electron microscopy, laser confocal microscopy, and x‐ray photoelectron spectroscopy revealed a surface morphology, average surface roughness, and surface composition similar to what has been previously reported for implants processed in the same manner …”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, both E2 treatment and microstructured Ti substrates are known to inhibit IL‐6 production while enhancing production of TGFβ1 and OPG (Kurebayashi et al, ; Lohmann et al, ; Schwartz et al, ). It was also shown that conditioned media from MSC cultures grown on microstructured Ti substrates for 7 days inhibit osteoclast activity and this is correlated with surface‐dependent production of osteoclast inhibitory factors (Lotz et al, ). In addition to the high production of negative regulators of osteoclast activity, cells produce high levels of osteocalcin and osteopontin (Lotz et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…The surface characteristics of titanium (Ti) implants affect cell adhesion, proliferation and osteoblast differentiation, which ultimately dictate the interfacial tissue formation to achieve implant fixation to the host and determine the success rate of dental implants . Modifications of Ti topography may affect osteoblast differentiation by acting on several cell mechanisms and signaling pathways, including those triggered by integrins …”
Section: Introductionmentioning
confidence: 99%